Quantification of mantle attachment scars on the Margaritifera margaritifera (Margaritiferidae, Bivalvia) shell - Zotin, A. A.; Ieshko, E. P. (Arctic Environmental Research, 2019)
A characteristic feature shared by all Margaritiferidae mussels consists in the presence of scars on the internal surface of their shells. These scars mark places of mantle attachment by specific epithelial cells. According to some authors, such parameters of mantle attachment scars as the density and degree of their manifestation can be used for the purposes of species identification. To this end, quality indicators (numerous or few, pronounced or poorly visible scars) are typically used; however, the use of quantitative criteria is preferable. This work was aimed at developing quantitative indicators of mantle attachment scars in the Margaritifera margaritifera freshwater pearl mussels for the populations of the Syuskyuyanyoki and Livoyoki rivers (Karelia). It is shown that the density and size of mantle attachment scars are approximately the same for all the investigated shell samples. These parameters display the absence of dependence on the age and size of molluscs. The regression coefficients for the linear dependence of the density or size of mantle attachment scars on the age or length of the shell show no significant difference from 0. For all the investigated molluscs, the density and size of mantle attachment scars are established to vary within the range of 0.37–1.16 scars/cm 2 (0.71 ± 0.03 scars/cm 2 on average) and 215–690 µm (417 ± 2 µm on average), respectively. According to a two-factor analysis of variance, the distribution of mantle attachment scars appears to be irregular across the shell surface. At the same time, a significant (p < 0.001) increase in their density is observed in the posterior and ventral directions, as well as diagonally in the posterior ventral direction. Issues associated with the application of the investigated parameters for the purposes of mollusc species identification are discussed.